Strategi Pengelolaan Kawasan Ekowisata Mangrove Berkelanjutan Di Taman Wisata Alam Teluk Yotefa Kota Jayapura. - Basa T. Rumahorbo (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
The concept of environmental management based on sustainability ecotourism is starting to be seen as important given the large amount of environmental damage. Until now the mangrove forest in Yotefa Jayapura Bay Nature Park has not been managed properly as an ecotourism destination, therefore a Mangrove Ecotourism Area Management Strategy is needed in Yotefa Jayapura Bay Nature Park. This study aims to analyze the management strategy for the mangrove ecotourism area in Hamadi Beach, Kota Jayapura using a qualitative approach with descriptive analysis and SWOT analysis. The results of the study show that based on observations through surveys, it is known that Mangrove forests, especially around the Yotefa Bay Nature Park, Jayapura. There are 4 strategies in managing the mangrove ecotourism area management strategy at Hamadi Beach, Jayapura City, namely: 1. Development of community-based ecotourism with support government through related agencies, 2. Providing comfortable and safe facilities and infrastructure and improving the arrangement of facilities that are lacking, 3. Increasing community participation in various activities related to mangrove forests and tourism, 4. Outreach to ecotourism activities for the community.